GEOELECTRICAL EXPLORATION FOR GROUNDWATER IN CRYSTALLINE BASEMENT ROCKS OF FOBUR AND ITS ENVIRONS, JOS-PLATEAU, NORTHCENTRAL NIGERIA - BULUS, J. A.; ALUWONG, K. C.; ODEWUMI, S. C.; ABALAKA, I. E.; KAZE, I. N. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
Fobur and its environs are underlain by crystalline rocks in the north-central sector of the Nigerian Basement Complex. A geophysical investigation involving electrical resistivity was carried out with the aim of evaluating the groundwater potential for alternative water supply due to inadequate surface water and low yield boreholes in the area. Thirty-three (33) Vertical Electrical Soundings (VES) were acquired from Fobur and its environs adopting Schlumberger electrode configuration with current electrode separation (AB) varying from 1.5 to 125 m. The acquired field data were interpreted and iterated using “RESIST” software. The total transverse resistance value (219.8 - 26721.50 Ωm2) was adopted in the classification of the area into poor, weak, moderate and very good transmissivity zones. The groundwater potential of Fobur and its environs are classified into poor, low and good groundwater potential zones based on the integration of geo-electric and Dar-Zarrouk parameters. The VES data indicate two (2) to five (5) geo-electric layers namely: topsoil/lateritic, clayey soil, weathered layer, fractured unit and fresh basement. The Overburden comprises of the topsoil, laterite, and weathered basement with thickness ranging from 3.6 to 42 m. The zones with overburden thickness of 20m and above are viable for groundwater abstraction and constitute about 50 % of the area. The aquifer protective capacity of the area was classified into good (> 0.7 mhos), moderate (0.2 – 0.69 mhos), weak (0.1 – 0.19 mhos), and poor (< 0.1 mhos), based on the longitudinal conductance value (0.00192 - 1.587868 mhos). The basement resistivity ranges from 43.7 to 27717.3 Ωm and was used to classify the area into good, medium, low and negligible aquifer potential zones. Hence, the result of this research will form the tools for groundwater improvement, management and structural/infrastructural development planning of the study area.